Determinants Of Purchasing Decisions In Tik Tok Shop E-Commerce With Trust As A Mediating Variable - Munadia, Milda; Umuri, Khairil; Sentosa, Dewi Suryani; Nurlina, Eka (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2024)
This study aims to examine the effect of security and Sharia compliance on purchasing decisions in the e-commerce TikTok Shop with trust as a mediating variable. The sample in this study were active undergraduate students at USK totaling 85 people who were taken based on the Hair formula and analyzed using the path analysis model. The results of this study found that security and sharia compliance had a positive effect on trust. Security, Sharia compliance, and trust have a positive effect on purchasing decisions. In the Sobel test, the indirect effect shows that security and Sharia compliance have a positive influence on purchasing decisions through trust as a mediating variable. Further research can take other supporting factors that have not been used in this study